Dynamic Factor Models and Fractional Integration – With an Application to US Real Economic Activity - Guglielmo Maria Caporale; Luis Alberiko Gil-Alana; Pedro José Piqueras Martínez (CESifo GmbH, 2024)
This paper makes a twofold contribution, First, it develops the dynamic factor model of Barigozzi et al. (2016) by allowing for fractional integration instead of imposing the classical dichotomy between I(0) stationary and I(1) non-stationary series. This more general setup provides valuable information on the degree of persistence and mean-reverting properties of the series. Second, the proposed framework is used to analyse five annual US Real Economic Activity series (Employees, Energy, Industrial Production, Manufacturing, Personal Income) over the period from 1967 to 2019 in order to shed light on their degree of persistence and cyclical behaviour. The results indicate that economic activity in the US is highly persistent and is also characterised by cycles with a periodicity of 6 years and 8 months.
Keywords: C22; E32; 330; fractional integration; dynamic factor models; persistence; business cycle; economic activity; Kalman filter; state-space models